Avaliação da política nacional de desenvolvimento de pessoal na Universidade Federal do Ceará com foco nos servidores técnico-administrativos em educação - Queiroz, Glicielle Bezerra de (2020)
This research aims to evaluate the execution of the National Personnel Development Policy at the Federal University of Ceará, with a focus on technical-administrative servers in education. The relevance of this theme arises in view of the changes promoted by the Brazilian Public Administration, which, when adhering to the management model, started to consider the improvement of servers to improve the provision of services to society. The choice of the Federal University of Ceará (UFC) as the location for this research is justified by the prominent position reached among similar institutions. The investigative intention comprises: a) analyzing the National Personnel Development Policy (PNDP) and the Career Plan for Technical-Administrative Positions in Education (PCCTAE); b) investigate the dynamics of PNDP execution at UFC; and c) understand the perceptions of technical-administrative servers in education from their experience with the PNDP at the institution. As for the methodology used, a qualitative approach was adopted with quantitative contributions, of an exploratory and descriptive character, whose methodological perspective of assessment is in line with the Experiential Model. The triangulation of methods was also used in order to understand the phenomenon studied from multiple dimensions. The results obtained point to a lack of compatibility between the rigidity of the structures present in the PCCTAE and the proposals of the PNDP. The assessment of the PNDP's execution dynamics at UFC revealed that the institution has expanded the offer of development actions, which has favored the increase in the number of participating civil servers, however, it still needs adjustments in order to identify the training needs. and the qualification of professionals, improving access to courses, making managers aware of the importance of development actions, taking advantage of the acquired competences and evaluating the return that the completion of courses brings to the professional practice of civil servers. The evaluation of the results of the qualitative and quantitative research allowed to infer that the TAE servers recognize that the participation in development actions improves their performance at work and that the existence of financial remunerations foreseen in the PCCTAE constitutes an element capable of motivating them to participate in these actions. However, they identify as barriers: lack of support from the leadership; difficulty accessing courses; and lack of use of competences in their work activities. Even so, TAE employees claim to be willing to take on new tasks, regardless of their position and financial remuneration. The results of this study may contribute as a source of information for the analysis and improvement of the actions related to the execution of the PNDP within the scope of the UFC itself or for the purposes of comparison and reproduction of best practices in other similar institutions.